2022
DOI: 10.3389/fmicb.2022.811774
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Profiling Specifies Involvement of Alternative Ribosomal Proteins in Response to Zinc Limitation in Mycobacterium smegmatis

Abstract: Zinc ion (Zn2+) is an essential micronutrient and a potent antioxidant. However, Zn2+ is often limited in the environment. Upon Zn2+ limitation, Mycolicibacterium (basonym: Mycobacterium) smegmatis (Msm) undergoes a morphogenesis, which relies on alternative ribosomal proteins (AltRPs); i.e., Zn2+-independent paralogues of Zn2+-dependent ribosomal proteins. However, the underlying physiological changes triggered by Zn2+ limitation and how AltRPs contribute to these changes were not known. In this study, we exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Thus, when GT is added to E. faecalis , we hypothesise that resultant zinc depletion would lead to zinc release from ribosomes and consequent increased presence of selected zinc-free ribosomal protein paralogs. Future RNAseq work will further investigate this GT-induced phenomenon in E. faecalis , as has been deployed in Mycobacterium smegmatis 55 . In the work of Dow et al, non-zinc-binding paralogs were identified as functional replacements for Zn 2+ -dependent paralogs and were involved in the transcriptomic response to Zn 2+ -limitation.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, when GT is added to E. faecalis , we hypothesise that resultant zinc depletion would lead to zinc release from ribosomes and consequent increased presence of selected zinc-free ribosomal protein paralogs. Future RNAseq work will further investigate this GT-induced phenomenon in E. faecalis , as has been deployed in Mycobacterium smegmatis 55 . In the work of Dow et al, non-zinc-binding paralogs were identified as functional replacements for Zn 2+ -dependent paralogs and were involved in the transcriptomic response to Zn 2+ -limitation.…”
Section: Resultsmentioning
confidence: 99%